LEFT SUBCLAVIAN ARTERY RUPTURE DUE TO BLUNT THORACIC TRAUMA: A CASE REPORT - Yopie Afriandi Habibie; Ign Wuryantoro (Universitas Syiah Kuala, 2018)
Abstract. Blunt thoracic trauma highest incidence is in adult, 20% to 50 % of the trauma cause death. Injuries to the vascular structures of the thoracic outlet, especially left subclavian artery, are rare and typically accompanied by massive hemorrhage. Close observation of vital sign and serial chest x-ray are very important. We describe an unusual presentation of a patient who suffered traumatic rupture ofleft subclavian artery. No clinical presentation of supraclavicular hematoma, unilateral absence of radial artery pulse and mediastinal widening in chest x-ray was found, but there is a massive hemothorax. Left posterolateral thoracotomy was performed, the source of bleeding was found in the apex of the lung, suspected a rupture of the left subclavian artery. The procedure continued with median sternotomy extended to left supraclavicular incision, a rupture was found in the left subclavian artery, 1,5 cm proximal to aortic arch. Primary repair was done with a good result. Key Words : Blunt thoracic trauma, massive hemothorax, left subclavian artery rupture